Enhancing capacity of research ethics review committees in developing countries: The Kenyan example - Gloria Manyonyi; Walter Jaoko; Kirana Bhatt; Simon Langat; Gaudensia Mutua; Bashir Farah; Jacquelyne Nyange; Joyce Olenja; Julius Oyugi; Sabina Wakasiaka; Maureen Khaniri; Keith Fowke; et al. (South African Journal of Bioethics and Law, 2014)
Background. The increased number of clinical trials taking place in developing countries and the complexity of trial protocols mandate that local ethics review committees (ERCs) reviewing them have the capacity to ensure that they are conducted to the highest ethical standards.Methods. The Kenya AIDS Vaccine Initiative (KAVI) Institute of Clinical Research (ICR) (KAVI-ICR) and the Kenyan National Council for Science and Technology (NCST) embarked on an exercise to enhance the capacity of ERCs in Kenya to review such protocols. This process involved conducting an audit of all ERCs in the country, and performing training needs assessments to identify knowledge and capacity gaps. Information obtained was used to develop training materials for ERC members at workshops conducted in different parts of the country.Results. Five accredited and 13 non-accredited ERCs were identified. Four of the accredited ERCs were located in the capital city of Kenya, Nairobi. The most common challenges cited by participants during the needs assessments were excess workload, and a lack of co-ordination and/or communication between the ERCs. Subsequently, 140 ERC members from 17 institutions across the country were trained as follows: 36 from institutions in the western part of Kenya, 38 from institutions in the south-eastern coastal region, 38 from the eastern region and 44 from Nairobi.Conclusion. The KAVI-ICR and the NCST have developed training modules for training ERC members in Kenya and are in the process of developing a manual to train members. The Kenyan experience may be used to enhance the capacity of ERCs in the East African region.